SOMATIC LESSONS AS A MEANS OF IMPROVING STUDENTS' PSYCHOPHYSICAL CONDITION (Physical Culture and Sport: Scientific Perspective, 2023)
The article is devoted to the study of the psychophysical state of students, namely "interoceptive awareness", which is relevant in the training of specialists in physical education and sports.Today's challenges in our lives require a clear understanding and control of one's psychophysical state, and also affect the "quality of life" and "academic resilience" of students. An important aspect of these studies is the determination of the student's current level of interoceptive awareness. Self-reports are the main method of assessment. Well-known scientists in the field use the "Multidimensional Assessment of Interoceptive Awareness Questionnaire" as the main tool, namely its new version "MAIA-2."The MAIA-2 contains in 37 questions and 8 domains: "Noticing," "Not-Distracting," "Not-Worrying," "Attention Regulation," "Emotional Awareness," "Self-Regulation," "Body Listening," "Trusting." In turn, the "Noticing" contains 4 (1, 2, 3, 4) questions; the "Not-Distracting" contains 6 (5, 6, 7, 8, 9, 10) questions; the "Not-Worrying" contains 5 (11, 12, 13, 14, 15) questions; the "Attention Regulation" contains 7 (16, 17, 18, 19, 20, 21, 22) questions; the "Emotional Awareness" contains 5 (23, 24, 25, 26, 27) questions; the "Self-Regulation" contains 4 (28, 29, 30, 31) questions; the "Body Listening" contains 3 (32, 33, 34) questions, and "Trusting" contains 3 (35, 36, 37) questions. In addition, all 6 "Not-Distracting" questions and 3 (11, 12, 15) out of 5 "Not-Worrying" questions are reverse scored. That is, the calculation formula is "point = 5 – x," where "x" is the "raw" score taken from the answer to a separate question.The purpose of the study is to evaluate "Noticing" (domain of interoceptive awareness) of first-year students of the Faculty of Health, Physical Education and Sports.
Keywords: interoceptive awareness; somatic education; somatic lessons; somatic movement; somatic movement education